Do More of What Makes You Happy? The Applicability of Signature Character Strengths and Future Physicians’ Well-Being and Health Over Time - Huber, Alexandra; Bair, Angela; Strecker, Cornelia; Höge, Thomas; Höfer, Stefan (Frontiers in Psychology, 2021)
Research on applying signature character strengths demonstrated positive effects on well-being, health and work behavior. Future health care professionals represent a group at risk for impaired well-being due to high study demands. This study investigates potential long-term protective effects on well-being. In total, 504 medical students participated in a longitudinal online study, with at least 96 providing complete data at all three time points (time lag: one year). Data on individual signature character strengths and their applicability, thriving (subjective and psychological well-being), work engagement, burnout, mental and physical health were collected. Longitudinal relations of signature character strengths’ applicability and well-being, mental and physical health were tested with cross-lagged panel analyses. Moreover, indirect longitudinal mediation effects via work engagement and emotional exhaustion were considered. Cross-lagged panel analyses demonstrated significant positive effects of thriving on signature character strengths’ applicability at later time points (β = .20 to .27) indicating that higher levels of well-being might be mandatory first to have access to one’s own signature character strengths in a naturalistic setting. Disentangling thriving, the effect was only significant for psychological well-being (t1-t2: β = .23; t2-t3: β = .27). Across all three time points, significant indirect effects via work engagement on the relation of the applicability of signature character strengths and well-being were identified (r = .15), whereas significant indirect effects on mental and physical health were only evident at t2 (both: r = .06) and t3 (mental health: r = .11). A longitudinal mediation analysis via work engagement revealed a significant indirect effect (a*b = .13). These results call for further research as previous studies showed that the applicability of signature character strengths affected well-being, not vice versa. The ‘broaden-and-build’ theory (positive emotions broaden one’s consciousness and hereupon individuals build new enduring resources and skills) and the assumption of well-being in a ‘top-down’ model (trait-like predisposition to interpret life experiences in positive ways coloring one’s evaluation of satisfaction in various domains accordingly) could possibly explain these novel results.